Thermal efficiency gains enabled by using CO2 mixtures in supercritical power cycles. (1st January 2022) - Crespi, F.; Rodríguez de Arriba, P.; Sánchez, D.; Ayub, A.; Di Marcoberardino, G.; Invernizzi, C.M.; Martínez, G.S.; Iora, P.; Di Bona, D.; Binotti, M.; Manzolini, G.
Abstract: The present paper explores the utilisation of dopants to increase the critical temperature of Carbon Dioxide (sCO2 ) as a solution towards maintaining the high thermal efficiencies of sCO2 cycles even when ambient temperatures compromise their feasibility. To this end, the impact of adopting CO2 -based mixtures on the performance of power blocks representative of Concentrated Solar Power plants is explored, considering two possible dopants: hexafluorobenzene (C6 F6 ) and titanium tetrachloride (TiCl4 ). The analysis is applied to a well-known cycle - Recuperated Rankine - and a less common layout - Precompression -. The latter is found capable of fully exploiting the interesting features of these non-conventional working fluids, enabling thermal efficiencies up to 2.3% higher than the simple recuperative configuration. Different scenarios for maximum cycle pressure (250–300 bar), turbine inlet temperature (550–700 ° C) and working fluid composition (10–25% molar fraction of dopant) are considered. The results in this work show that CO2 -blends with 15–25%(v) of the cited dopants enable efficiencies well in excess of 50% for minimum cycle temperatures as high as 50 ° C. To verify this potential gain, the most representative pure sCO2 cycles have been optimised at two minimum cycle temperatures (32 ° C and 50 ° C), proving the superiority of the proposed blended technology in high ambient temperature applications. Graphical abstract: Image 1 Highlights: CO2 blends enable thermal efficiencies higher than 50% at high ambient temperatures. For a given layout, sCO2 blends enable 4–5 pp higher efficiency than pure sCO2 cycles. Precompression is the most interesting layout to better exploit CO2– C6F6 blends. The composition of the best-performing blend depends on ambient temperature. Cycle layout and dopant composition/fraction are independent optimisation variables.